In Search of Magic Bullets. (April 2016) - Freudenheim, Tom
Abstract: The author suggests that especially in museums, particularly art museums, creating truly visitor‐friendly environments eludes most institutions. The special, sometimes magical, experience of direct contact with original works of art can be encouraged by management decisions that make the museum a more accessible place. This ranges from technological fixes to simply insisting on friendliness from staff. Examples from the author's experience are provided.